173 Early Results of a Variable-Angle Volar Locking Plate for Distal Radius Fractures: A Bi-Centre Study. (4th May 2021) - Elerian, S; Singh, T; Jagodzinski, N A; Norris, R; Tan, S; Power, D; Jones, J; Rajaratnam, V
Abstract: Introduction: This study examines the clinical, functional and radiological outcomes of distal radius fracture fixation with the Aptus® (Medartis, Pennsylvania) locking plate in order to determine its efficacy and to identify notable findings related to treatment variations. Method: This is a retrospective bi-centre study collecting patient details from a District General Hospital and a Regional Hand Unit. We assessed 61 consecutive patients with distal radius fractures (AO grade A = 19, B = 9, C = 33) fixed using Aptus® plate with a minimum of six months follow-up. Outcome measures included the DASH score, wrist range of movement and grip strength, and complications. Radiographs were reviewed to assess restoration of anatomy and union. Results: All but two fractures united within six weeks. Mean ranges of movement were only mildly restricted compared to the normal wrist (flexion/extension = 102°; radial/ulna deviation = 53°; pronation/supination = 169°). Mean postoperative grip strength was 23.8kg which was comparable to the contralateral side at 31.5kg. The mean DASH score was 18.2. Seven patients had screws misplaced outside the distal radius although three of these remained asymptomatic. Conclusions: Variable-angle locking systems benefit from flexibility of implant positioning and may allow enhanced inter-fragmentary reduction for accurate fixation of intra-articular fractures.